Vendor Selection using Analytical Network Process (ANP) in Heavy Equipment Company - M. Yanie Syafei; Anastasya Lidya Maukar; Hening Herziatra (Faculty of Business, President University, 2018)
Using qualitative interviews to understand the mindset of family business leaders in succession, this Supply Chain Management is important in industry. Vendor is the key component in the supply chain flow. A company abbreviated as UTPE is one of the biggest manufacturing companies in Indonesia that produces heavy equipment. The main materials are plates and spare parts that have been supplied by eight vendors. The current system of vendor selection is based on tardiness of delivery time, but every vendor has different frequency of delivery so that it cannot be compared. Therefore, the appropriate criteria and sub criteria are required to create a new system of vendor selection. The criteria and sub criteria are determined based on the previous research and interview with an expert in the company. There are 5 criteria and 17 sub criteria that are approriate for vendor selection. ANP is the development of Analytical Heuristic Process (AHP) by considering dependency between elements of hierarchy. By using ANP, the interdependency between criteria, sub criteria and their weight can be defined. Data collection is done by using observation, interview and questionnaire. Sub criteria long term relationship has the highest weight and vendor abbreviated as GH is the best vendor with score 3.057 of 5.